Sinergi Kedaulatan Ilahi Dan Usaha Manusia: Analisis Struktur Paralelisme Dan Kiasmus Dalam Mazmur 127 - Andrian, Denis; Sualang, Farel Yosua (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2024)
Psalm 127 emphasizes the importance of man depending on God in all aspects of life. While most researchers, including Subagyo H, identify “Family” as the main theme, this article offers a different interpretation. This study reveals the content of the theme “Synergy between God's Sovereignty and Human Effort” as the core of Psalm 127. Using a qualitative approach, the study analyzes the structure and language patterns of the text, applying Robert Lowth's concept of parallelism to identify relationships between lines. It also considers the historical and cultural context in which the Psalm was written, as well as its impact on the choice of language and structure of the poem. The results are first, verse 1 through synonymous parallelism affirms the recognition of God's intervention without negating human effort; second, the antithetical parallelism in verse 2 shows the relationship between human effort and the time or circumstance that triggers God's blessing; third, the synthesizing parallelism in verses 3-5 illustrates God's trust in man's duty in educating children in youth. The understanding of the synergy between God's sovereignty and human effort revealed through this analysis provides a new perspective in interpreting Psalm 127.